Crystal Forming Rate and Distribution Changes of MCT Content in Palm Kernel Oil Fractionation Product - Mursalin, Mursalin; Yernisa, Yernisa (PUI BiGME Universitas Jambi, 2021)
Palm kernel oil is considered a special oil since it contains medium chain tryglicerides (MCT), especially lauric acid that is easily digested and has a special character as cocoa butter substitutes (CBS). Palm kernel oil fractionation will produce a solid fraction (stearin) and a liquid fraction (olein) with specific characteristics (specialty fat) that the physico-chemical properties are highly dependent on the cooling treatment applied. In this research, 3 kinds of crystallization temperatures (18.0 oC, 19.0 oC, dan 20.0 oC) in various cooling rates and duration of the crystallization process, were examined for its effect on the crystal-forming rate of palm kernel oil and distribution changes of MCT content of fraction resulted. All tracks recorded during the cooling process had to be calculated to predict the crystal-forming rate in the crystallization process. In all cooling treatments, the amount of olein fraction produced decreased and the stearin fraction increased which was equal to the duration of the crystallization process. The setting of crystallization temperature at 18.0 oC produced a stearin forming rate higher than at temperatures of 19.0 and 20.0 oC. Forming rate of stearin (crystal) was contrary to the crystallization temperature and duration of the cooling period but not being affected by initial cooling temperature, initial cooling rate, duration of the cooling process to reach crystallization temperature, and average rate of oil cooling. Percentage of oil crystal-forming at 3 crystallization temperature equals to logarithmic of crystallization duration. The lower the crystallization temperature, the higher the rate of oil crystallization forming. As the increase of stearin produced during crystallization, MCT content was decreasing, but for olein, as the decreasing it during the crystallization period, the distribution of MCT content tends to increase.